Perception by state and municipal authorities of innovations implemented in government bodies (based on the materials of the Republic of Tatarstan) - V.M. Akhmerova; A.M. Idiatullina (Векторы благополучия: экономика и социум)
The article analyzes the introduction of innovations in the field of public and municipal administration (using the example of the Ministry of Labor, Employment and Social Protection of the Republic of Tatarstan, the Ministry of Digital Development of Public Administration, Information Technology and Communications of the Republic of Tatarstan, MCU "Administration of the Sovetsky district of Kazan", MCU "Administration of the Vakhitovsky and Privolzhsky districts of Kazan"). Relevance. Introducing innovations into various spheres of state and municipal administration, as well as into the professional activities of state civil and municipal employees, necessitate certain training of employees and the development of a set of measures aimed at forming employees' innovative receptivity. In addition, government and municipal employees in modern realities are required not only to be passive implementers of innovations, but also their active initiators and developers. It is also indisputable that for the successful implementation of any innovations, it is necessary to have a clear understanding of the goals of their implementation and a competent team of performers. Aim. To identify and analyze the innovative receptivity of state civil and municipal employees of the republic. The subject of the research is the innovative receptivity of Tatarstan government personnel. Methods. Survey method implemented using the Yandex Forms service, on the basis of which the factors influencing innovation in government were identified, the attitude of state civil and municipal employees to innovation was revealed, and the reasons for this attitude of respondents to innovation were analyzed. Results. We have determined that innovations in the state and municipal authorities of the Republic of Tatarstan are a regular phenomenon affecting various aspects of the functioning of government bodies and the professional activities of state and municipal employees. It was revealed that the level of receptivity of innovations by employees is quite high and they consider them necessary.